Kondisi Psikologis Wanita Dewasa Madya Anak Pensiunan Abdi Negara Yang Belum Menikah - Sihombing, Firly Syahira; Saragi, Muhammad Putra Dinata (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research aims to determine the psychological condition of middle-aged women who are children of retired state servants who are not yet married. This research uses qualitative research with a descriptive approach. The subjects of this research were 3 (three) middle-aged women, unmarried children of retired state servants. The supporting informants in this study were 3 (three) individuals other than the subjects studied. The research was conducted at the Medan Kodam I/BB Dormitory. Data collection techniques were obtained through observation, interviews and documentation. The data analysis technique uses domain analysis which is carried out starting from reducing data, presenting data, and drawing conclusions. Research findings have shown that middle-aged women, children of retired state servants, have different psychological conditions and can be viewed from cognitive, emotional and interpersonal relationship aspects, namely two subjects have poor psychological conditions and one subject has good psychological conditions. The indicator of success for the three subjects is getting closer to Allah Swt. understand the wisdom of marriage, and accept oneself positively. Suggestions that can be put forward are so that research subjects can understand the wisdom of marriage which is supported by seeking happiness from within themselves and outside themselves and for future researchers to be able to look for other variables by finding something new about unmarried middle adult women.